2012
DOI: 10.1053/j.gastro.2012.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Mutations That Alter Use of Hepatitis C Virus Cell Entry Factors Mediate Escape From Neutralizing Antibodies

Abstract: BACKGROUND & AIMS The development of vaccines and other strategies to prevent hepatitis C virus (HCV) infection is limited by rapid viral evasion. HCV entry is the first step of infection; this process involves several viral and host factors and is targeted by host-neutralizing responses. Although the roles of host factors in HCV entry have been well characterized, their involvement in evasion of immune responses is poorly understood. We used acute infection of liver graft as a model to investigate the molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 45 publications
(91 reference statements)
7
89
0
Order By: Relevance
“…Our work supports prior more limited studies showing that HCVcc and HCVpp with identical E1E2 have similar relative neutralization resistance (Bailey et al, 2015a;Fofana et al, 2012;Swann et al, 2016;Urbanowicz et al, 2015). Importantly, to our knowledge, this is the first study to show this correlation using a diverse panel of human bNAbs targeting distinct epitopes across E1E2 and a large panel of diverse natural E1E2 variants, suggesting that these results are broadly applicable to other E1E2 variants and other antibodies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our work supports prior more limited studies showing that HCVcc and HCVpp with identical E1E2 have similar relative neutralization resistance (Bailey et al, 2015a;Fofana et al, 2012;Swann et al, 2016;Urbanowicz et al, 2015). Importantly, to our knowledge, this is the first study to show this correlation using a diverse panel of human bNAbs targeting distinct epitopes across E1E2 and a large panel of diverse natural E1E2 variants, suggesting that these results are broadly applicable to other E1E2 variants and other antibodies.…”
Section: Discussionsupporting
confidence: 88%
“…Neutralization results obtained using HCVcc and HCVpp have generally been similar (Fofana et al, 2012;Meunier et al, 2005;Scheel et al, 2008;Swann et al, 2016;Urbanowicz et al, 2015), but comparisons of specific infectivity and neutralization of HCVpp and HCVcc expressing genetically identical E1E2 variants have previously been performed only on a fairly limited basis, and to our knowledge neutralization of E1E2-matched HCVpp and HCVcc has never been compared using a diverse panel of bNAbs targeting distinct epitopes.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the development of an effective vaccine requires a detailed understanding of viral evasion from host immune responses, including nAbs. Previous studies investigating the molecular mechanisms of HCV liver graft infection, identified a viral variant termed VL 5,6 with efficient escape from patient nAbs. 5,6 Functional genetics had identified phenylalanine at HCV polyprotein residue 447 as being important for neutralization escape.…”
Section: H Epatitis C Virus (Hcv) Is a Major Health Problem Infectingmentioning
confidence: 99%
“…Previous studies investigating the molecular mechanisms of HCV liver graft infection, identified a viral variant termed VL 5,6 with efficient escape from patient nAbs. 5,6 Functional genetics had identified phenylalanine at HCV polyprotein residue 447 as being important for neutralization escape. 6 This amino acid is widely conserved among HCV isolates, as shown by its prevalence of 98.4% in all genotypes (including Jc1, Japanese fulminant hepatitis virus [JFH1], and H77) and 96.2% in genotype 1b strains (including VL).…”
Section: H Epatitis C Virus (Hcv) Is a Major Health Problem Infectingmentioning
confidence: 99%
See 1 more Smart Citation